Halal Value Chain Model In Pesantrenpreneur Ecosystem - Safarinda Imani; Imamatin Listya Putri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This research aims to analyze the halal value chain model of the Salafiyah and Syafi'iyah Musa'adah Sukorejo Islamic boarding school cooperatives. This field research uses a qualitative approach with a non-positivist paradigm and emphasizes understanding social reality. The data source in this research uses primary and secondary data. Primary data is in-depth interviews with three informants, while secondary data is a literature study. Data analysis uses three stages: data reduction, descriptive and evaluation, and concluding. The research results show that the Salafiyah Syafi'iyah Musa'adah Sukorejo Islamic boarding school cooperative has implemented effective and efficient halal value chain management by Sharia principles. It is identified in the formation of halal products that have implemented a halal value chain model starting from Sharia principles' production, distribution, and consumption processes. Theoretically, this research can be an additional reference for researchers and academics looking at the halal value chain of Islamic boarding school cooperatives. Practically, this research can inspire managers of other Islamic boarding school cooperatives to implement the halal value chain model.